GURU HONORER DAN PEKERJAANNYA (Analisis Tindakan Sosial Guru Honorer Dalam Bekerja Sebagai Guru di SMPN 4 Bangko Pusako Kecamatan Bangko Pusako Kabupaten Rokan Hilir) - ", Warsini; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research has done at SMPN 4 Bangko Pusako Bangko Pusako sub - district Rokan Hilir Regency that the aim was to find out the rationality work background as a teacher and also survive as honorary teacher has taught more than ten years. The method used descriptive qualitative research design. The subject was 4 honorary teachers as informant and a principal as the key informant. In the process of data collection, observation, interview, and documentation were used. The descriptive analyses shown that the work background as honorary teacher was caused by the parents’ motivation, the advantage; there was religious value and the goals. The result observation showed that teacher who as honorary teacher has different motivation, so every honorary teacher has taught more than 10 years also has different action rationality. There was honorary teacher has taught by the instrumental action rationality however by the time it changed to be value rationality, but also there was teacher that survived by the irrational tradition and irrational affection since the beginning. By the different action rational and different hopes so that they survive in teaching to be a civil servant, the honorary teacher’s prosperity as a teacher,   to educate the students, and as the charity.    Keywords: Rationality, Honorary teacher.